Potential Effectiveness of Registered Dietitian Nutritionists in Healthy Behavior Interventions for Managing Type 2 Diabetes in Older Adults: A Systematic Review - Dobrow, Laurel; Estrada, Isabella; Burkholder-Cooley, Nasira; Miklavcic, John (Frontiers in Nutrition, 2022)
Purpose: A systematic review was conducted to assess how the involvement of a Registered Dietitian Nutritionist (RDN) in healthy behavior interventions (HBIs) potentially affects outcomes in older adults with type 2 diabetes (T2D). Methods: Literature was searched for primary research published between 2016 and 2020 on HBI involving a RDN affecting outcomes in older adults with T2D. Evaluations of hemoglobin A1c (HbA1c), blood glucose, blood pressure, cholesterol, anthropometry, body composition, medication usage, healthcare cost, and self-efficacy and/or adherence to healthy behaviors outcomes were selected for inclusion. All literature included were summarized, evaluated for certainty of evidence criteria, and assessed for bias. Results: A total of 12 studies were included for assessment. Involvement of a RDN in HBI was shown to reduce HbA1c, fasting blood glucose, LDL cholesterol, and blood pressure; and improve lean body mass, BMI, and self-efficacy in populations of older adults with T2D. Compared to older adults with T2D receiving HBI involving RDNs, patients receiving usual care may incur higher healthcare costs or longer hospital stays. There was a high certainty of evidence for RDN involvement in HBI with regards to reduction in HbA1c. There was a moderate certainty of evidence for RDN involvement in HBI with regards to favorable changes in weight or body composition and cardiometabolic health outcomes. Statistically significant improvements in outcomes were usually sustained in follow-up after conclusion of HBI. Conclusions: RDNs may play an integral role in HBIs resulting in improved glycemic control, weight management, cardiovascular outcomes, and presumably comorbidity management. RDNs are important facilitators of diet education and nutrition assessment which are essential in T2D management and should therefore be considered for routine inclusion in interprofessional teams for improved outcomes in older adults with T2D.